Pengalaman Kerja, Independensi, Integritas, Kompetensi dan Pengaruhnya terhadap Kualitas Audit - Zezen Evia; R Ery Wibowo Santoso; Nurcahyono Nurcahyono (Universitas Muhammadiyah Jakarta, 2022)
This study aims to empirically prove the effect of work experience, independence, integrity and competence on audit quality. This study employs quantitative method with primary data derived from all auditors who work in Public Accountant Office at Semarang City selected with convenience sampling. The results show that work experience, independence, integrity, and competence partially have a significant positive effect on audit quality. Thus, Public Accounting Firms in improving audit quality must pay attention to audit experience, independence, integrity, and competence of an auditor.